2015
DOI: 10.3109/03602532.2015.1105253
|View full text |Cite
|
Sign up to set email alerts
|

MRP1 and its role in anticancer drug resistance

Abstract: The phenomenon of multidrug resistance (MDR) in cancer is associated with the overexpression of the ATP-binding cassette (ABC) transporter proteins, including multidrug resistance-associated protein 1 (MRP1) and P-glycoprotein. MRP1 plays an active role in protecting cells by its ability to efflux a vast array of drugs to sub-lethal levels. There has been much effort in elucidating the mechanisms of action, structure and substrates and substrate binding sites of MRP1 in the last decade. In this review, we deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 157 publications
2
95
0
Order By: Relevance
“…Previous studies have compiled numerous reports on the key role of MRP1 in MDR (15)(16)(17)27). In the present study, it was demonstrated that MRP1 is negatively regulated by miR-134, and that FOXM1 siRNA significantly downregulated MRP1 expression in lung adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have compiled numerous reports on the key role of MRP1 in MDR (15)(16)(17)27). In the present study, it was demonstrated that MRP1 is negatively regulated by miR-134, and that FOXM1 siRNA significantly downregulated MRP1 expression in lung adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 60%
“…The alteration of MRP1 expression has previously been associated with certain lung diseases, and this protein may be pivotal in protecting the lungs via its ability to efflux an array of drugs to sub-lethal levels (26,27). Previous studies have compiled numerous reports on the key role of MRP1 in MDR (15)(16)(17)27).…”
Section: Discussionmentioning
confidence: 99%
“…63 Thus, the presence of a spiro-cyclopropyl substituent at the 4-position of the pyrrolidine ring has been found to contribute not only to enhancing potency and improving protein-adjusted EC 50 values, but also to a notable PK profile in monkeys ( Figure Figure 19. 66 To address this metabolic liability of 43, these investigators replaced the dimethylamino ethyl substituent at N 1 of the benzimidazole ring with the butyronitrile moiety and the bulky substituent at benzimidazolone ring with a small substituent (e.g., isopropyl) to yield compound 44, having 19 excellent antiviral potency and Caco-2 permeability as shown in Figure 19.…”
Section: Compound 38 (Simeprevir/olysio): Compound 38 (Tmc435/simeprementioning
confidence: 95%
“…Previous studies have found that higher MRP1 expression could confer MDR in various cancers including breast cancer [10,11]. For instance, enforced expression of MRP1 enhanced adriamycin (ADR) chemoresistance of prostate cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%